Design, Synthesis, and Antipoliferative Activities of Novel Substituted Imidazole-Thione Linked Benzotriazole Derivatives - Ahdab N. Khayyat; Khaled O. Mohamed; Azizah M. Malebari; Afaf El-Malah (Molecules, 2021)
A new series of benzotriazole moiety bearing substituted imidazol-2-thiones at N1 has been designed, synthesized and evaluated for in vitro anticancer activity against the different cancer cell lines MCF-7(breast cancer), HL-60 (Human promyelocytic leukemia), and HCT-116 (colon cancer). Most of the benzotriazole analogues exhibited promising antiproliferative activity against tested cancer cell lines. Among all the synthesized compounds, BI9 showed potent activity against the cancer cell lines such as MCF-7, HL-60 and HCT-116 with IC50 3.57, 0.40 and 2.63 µM, respectively. Compound BI9 was taken up for elaborate biological studies and the HL-60 cells in the cell cycle were arrested in G2/M phase. Compound BI9 showed remarkable inhibition of tubulin polymerization with the colchicine binding site of tubulin. In addition, compound BI9 promoted apoptosis by regulating the expression of pro-apoptotic protein BAX and anti-apoptotic proteins Bcl-2. These results provide guidance for further rational development of potent tubulin polymerization inhibitors for the treatment of cancer.